Self regulation in Quranic learning - Hanafi, Yusuf; Murtadho, Nurul; Hassan, Abd Rauf; Saefi, Muhammad; Ikhsan, M. Alifudin; Tsania Nur Diyana (Universiti Utara Malaysia Press, 2021)
Purpose – The emergence of academic anxiety and poor learning outcomes among Indonesian first-year students at higher education institutions emphasized the need to measure the level of self-regulated learning (SRL). This study was part of a larger SRL research project in the area of ​​learning Qur’an recitation, where we attempted to explore further on how students applied SRL. By using a new perspective of SRL as a social process that emphasized interaction, we investigated how the situated environment influenced learning. Method – Quantitative and qualitative approaches were applied. A set of questionnaires generated from the adaptation process was successfully validated through rigorous psychometric testing. A total of 420 first-year students responded to the questionnaire. Then semi-structured observations and interviews were conducted among eight students. Finally, data obtained from observation checklists and interviews were triangulated. Findings – The SRL level for first-year students in learning Qur’an recitation was insufficient, with a score of 3.37 out of 5.00. The highest score on the Meta-Affective dimension was M = 3.64, and the lowest score on the Sociocultural-Interactive dimension was M = 2.98. These results indicated that although anxiety was not a serious problem, yet it was still an obstacle for some students with low SRL to achieve targeted learning goals. Furthermore, these students did not have the awareness to seek help for their learning difficulties. This situation was further aggravated by the lack of assistance from instructors in creating conducive learning environments for students to interact with each other. Significance – The standard deviations on all SRL dimensions identified in this study were high, showing a large gap between students who had high and low SRL. This condition requires instructors to provide significant assistance. We suggest heterogeneous grouping to enable more intensive interactions between students to increase the sociocultural-interactive dimension. We believe that seamless interaction is the most tangible support for promoting SRL.